Assembly of cerium-based coordination polymer into variant polycrystalline 2D–3D CeO2−x nanostructures. Issue 9 (14th January 2020) - S. Mofarah, Sajjad; Adabifiroozjaei, Esmaeil; Wang, Yuan; Arandiyan, Hamidreza; Pardehkhorram, Raheleh; Yao, Yin; Assadi, M. Hussein N.; Mehmood, Rashid; Chen, Wen-Fan; Tsounis, Constantine; Scott, Jason; Lim, Sean; et al.
Abstract : The present work reports a simple and rapid disassembly/reassembly approach at room temperature to tailor functional metal oxides of 2D and 3D architectures. Abstract : Precise control over the morphology of nanomaterials is critical yet challenging. The present work reports an efficient approach to tailor the architecture of nanostructures. The process involves rapid disassembly/reassembly of an unstable metal-based coordination polymer (MCP) by controlling the kinetics of the reassembly process. The synthesis procedure delivers unprecedented polycrystalline nanostructures, e.g., holey 2D CeO2− x nanosheets, with precisely tailored thicknesses in the range of 10–100 nm, and hollow 3D pseudo-octahedra and spheres. The consequent high surface areas and pore volumes, short diffusion distances, and high defect densities of the holey 2D CeO2− x indicate significant densities of active sites. This holey architecture exhibits rapid CO conversion and outstanding solar light photocatalytic performance. This approach of directed assembly offers a template-free, controllable, and cost-effective approach to achieve engineered CeO2− x architectures, which are nearly impossible through existing approaches.